Evolutionary, paleoecological, and biostratigraphic implications of the Ediacaran-Cambrian interval in West Gondwana - Warren, Lucas V. [UNESP]; Inglez, Lucas [UNESP]; Xiao, Shuhai; Buatois, Luis A.; Mángano, M. Gabriela; Okubo, Juliana [UNESP]; Alessandretti, Luciano; Simões, Marcello G. [UNESP]; Riccomini, Claudio; Antunes, Gabriel C. [UNESP]; Cerri, Rodrigo I. [UNESP]; Bahniuk, Anelize R.; et al. (Geological Society of America, 2023)
The Ediacaran-Cambrian transition interval is described for the west part of the Gondwana Supercontinent. This key interval in Earth’s history is recorded in the upper and lower part of the Tagatiya Guazú and Cerro Curuzu formations, Itapucumi Group, Paraguay, encompassing a sedimentary succession deposited in a tidally influenced mixed carbonate-siliciclastic ramp. The remarkable presence of cosmopolitan Ediacaran shelly fossils and treptichnids, which are recorded in carbonate and siliciclastic deposits, respectively, suggests their differential preservation according to lithology. Their distribution is conditioned by substrate changes that are related to cyclic sedimentation. The associated positive steady trend of the δ13C values in the carbonate facies indicates that the Tagatiya Guazú succession is correlated to the late Ediacaran positive carbon isotope plateau. Sensitive high-resolution ion microprobe U-Pb ages of volcanic zircons from an ash bed ∼30 m above the fossil-bearing interval in the Cerro Curuzu Formation indicate an Early Cambrian (Fortunian) depositional age of 535.7 ± 5.2 Ma. As in other coeval sedimentary successions worldwide, the co-occurrence of typical Ediacaran skeletal taxa and relatively complex trace fossils in the studied strata highlights the global nature of key evolutionary innovations.